The population of spotted cuscus (Spilocuscus maculatus) and its habitat carrying capacity in Numfor Island, Papua, Indonesia - ANTON SILAS SINERY; WARTIKA ROSA FARIDA; JACOB MANUSA WAI (Society for Indonesian Biodiversity, 2016)
Sinery AS, Farida WR, Manusawai J. 2016. The population of spotted cuscus (Spilocuscus maculatus) and its habitat carrying capacity in Numfor Island, Papua, Indonesia. Biodiversitas 17: 315-321. The purpose of this research was to study the population of spotted cuscus (Spilocuscus maculatus) and the carrying capacity of its habitat. The result showed that the cuscus population size in 105 ha research area was 17 individuals, with population density of 0.41 individuals/ha or each individual occupied 2.44 ha. Cuscus is the first consumer in a food chain system that consumes a variety of plants and plays an important role in the spread of plant seeds. Its birth rate is higher than its death rate despite its low reproduction rate. Fruit-bearing trees with diameter > 10 cm as source of food for cuscus consisted of 13 species of 10 families with a diversity index of 2.43 (categorized as moderate). The productivity of cuscus food was 0.75 kg/season/ ha which indicated the limitations of the carrying capacity of cuscus’ habitat so that the need of food was fulfilled from secondary forests and community gardens.